Fabrication of Na‐Ion Full‐Cells using Carbon‐Coated Na3V2(PO4)2O2F Cathode with Conversion Type CuO Nanoparticles from Spent Li‐Ion Batteries. Issue 6 (24th April 2022) - Subramanyan, Krishnan; Akshay, Manohar; Lee, Yun‐Sung; Aravindan, Vanchiappan
Abstract: Spent lithium‐ion batteries (LIBs) offer immense potential in the form of resources such as Li, transition metals (Co, Ni, and Mn), graphite, and Cu, which can be recovered through suitable recycling procedures. The Cu‐current collector is recovered from spent LIBs and converted as a copper oxide (CuO) anode for Na‐ion batteries. The performance of CuO is evaluated with carboxymethyl cellulose (CMC) (CuO–C), and polyvinylidene fluoride (PVdF) (CuO–P) binders in CuO half‐cell and CuO/carbon‐coated Na3 V2 (PO4 )2 O2 F (CuO/NVPOF) full–cell assemblies. The CuO–C half‐cell displays superior electrochemical performance than CuO–P in terms of cycling and rate performance showing 88% more capacity. To study the stabilization and solid electrolyte interphase growth in CuO–C, an in situ impedance study is conducted. However, the full‐cell, CuO–P/NVPOF displays better capacity retention during cycling with Coulombic efficiency >95% from the second cycle, whereas CuO‐C/NVPOF could hardly maintain only >90%. For conversion type CuO, it is apparent that, though the CMC binder supports half‐cell performance, the PVdF binder is suitable for the practical cell/full‐cell configuration. Abstract : Copper current collector from spent Li‐ion batteries has been upcycled into CuO nanoparticles via a simple and scalable process and evaluated as an anode for Na‐ion batteries. The electrochemical performance of the CuO anode is evaluated in half‐cell and full‐cell configurations (CuO/NVPOF) with two different binders. CuO half–cell with CMC binder shows improved Coulombic efficiency and robust high current performance.